Profitability, Sales Growth, Ownership Structure on Company Value with Moderation of Capital Structure in Fisihing Company - Kartikasari, Rachma; Sihombing, Pardomuan (Asean International Journal of Business, 2024)
This research aims to test and analyze the influence of profitability, sales growth, managerial ownership and institutional ownership on company value with capital structure as a moderating variable in fishing companies. This research uses quarterly financial report data obtained from 8 fishing companies listed on the Indonesia Stock Exchange (BEI) for the period from Quarter I 2020 to Quarter III 2023. The sampling technique in this research uses Saturated Sampling Technique with 8 fishing companies selected as sample. This research uses panel data analysis techniques with moderated regression analysis (MRA) on E-views 13. The research results prove that profitability, managerial ownership and capital structure have a positive effect on company value, while sales growth and institutional ownership have no effect on company value. In addition, capital structure is able to moderate profitability on company value.